Penerapan Evidence-Based Nursing Practice dengan Constraint-Induced Movement Therapy pada Pasien Stroke Iskemik: Studi Kasus: Application of Evidence-Based Nursing Practice Using Constraint-Induced Movement Therapy in Ischemic Stroke Patients: A Case Study - Suranta, Tomi; Sihombing, Riris Yuniwaty; Virgona, Argi; Untari, Diah (Chakra Brahmanda Lentera Institute, 2026)
Stroke is one of the leading causes of disability and mortality worldwide, resulting in a significant decline in patients’ quality of life. In ischemic stroke, impairment of upper extremity motor function and limitations in activities of daily living (ADL) are common and require comprehensive, evidence-based nursing care. This study aimed to describe the implementation of nursing care for patients with ischemic stroke through the application of Evidence-Based Nursing Practice (EBNP) using the Constraint-Induced Movement Therapy (CIMT) intervention. This study employed a descriptive case study design involving one patient with subacute ischemic stroke who was hospitalized in an inpatient care unit. The observed variables included upper extremity motor function of the paretic side and the level of independence in activities of daily living. The CIMT intervention was administered in a structured manner for 30–60 minutes per session, 1–2 times per day for five consecutive days. Muscle strength was assessed using Manual Muscle Testing (MMT), while independence in activities of daily living was measured using the Barthel Index before and after the intervention. The results demonstrated an improvement in upper extremity motor function of the paretic limb, as indicated by increased muscle strength and enhanced functional movement ability. In addition, an increase in the Barthel Index score reflected an improvement in the patient’s level of independence in performing activities of daily living. The application of EBNP through CIMT was proven to be effective in improving motor function and independence among patients with ischemic stroke. This intervention can be recommended as part of rehabilitative nursing care in the subacute phase of ischemic stroke to support functional recovery and enhance patients’ quality of life.